2008
DOI: 10.4049/jimmunol.180.2.774
|View full text |Cite
|
Sign up to set email alerts
|

ICOS Controls the Pool Size of Effector-Memory and Regulatory T Cells

Abstract: ICOS is an important regulator of T cell effector function. ICOS-deficient patients as well as knockout mice show severe defects in T cell-dependent B cell responses. Several in vitro and in vivo studies attributed this phenomenon to impaired up-regulation of cell surface communication molecules and cytokine synthesis by ICOS-deficient T cells. However, we now could show with Ag-specific T cells in a murine adoptive transfer system that signaling via ICOS does not significantly affect early T cell activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
230
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(265 citation statements)
references
References 39 publications
(41 reference statements)
27
230
1
5
Order By: Relevance
“…Finally, costimulation with DLL4-Fc elevated both mRNA and cell surface levels of ICOS (inducible T-cell costimulator) (Fig. 4 E and F), a receptor implicated in control of CD4 + effector cell survival (32). In summary, Notch activates a broad gene expression program to protect activated CD4 + T cells from cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, costimulation with DLL4-Fc elevated both mRNA and cell surface levels of ICOS (inducible T-cell costimulator) (Fig. 4 E and F), a receptor implicated in control of CD4 + effector cell survival (32). In summary, Notch activates a broad gene expression program to protect activated CD4 + T cells from cell death.…”
Section: Resultsmentioning
confidence: 99%
“…46 On the contrary, these molecules as well as ICOS also facilitate the expansion of T reg cells. 36,45,47 B cells of aged BWF1 mice, however, did not show significant expression of ligands for these co-stimulatory molecules (data not shown). This observation implies that reversal of the suppression, if any, might take place through the other pathway(s).…”
Section: Discussionmentioning
confidence: 99%
“…30 It has been shown that ICOS critically controls the pool size of both effector memory and regulatory T cells. 31 In our study, comprising the global cohort of 77 patients, no significant changes in the frequency of ICOS C CD4 C T and CD8 C T cells from baseline to week 6 were observed (Fig. S2).…”
Section: Ipilimumab Induces Early Immunological Changes Of T Cell Submentioning
confidence: 93%